Pangeran Diponegoro dalam Perang Jawa 1825-1830 - Vira Maulisa Dewi (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2020)
The Javanese war which erupted from 1825-1830 was one of the events that became the starting point of the beginning of colonialism in Java. The Javanese war became one of the major changes in the world in the late 18th and early 19th centuries. For the Javanese, especially in Surakarta and Yogyakarta, these periods were times that showed a decline in the Javanese order, especially in the palace. In addition, Dutch interference which was increasingly uncontrolled further worsened the situation. In Yogyakarta where Prince Diponegoro grew up to become a prince, this deterioration was increasingly apparent before the seconds of the Java War erupted. In the Java War, Prince Diponegoro served as one of the most important historical actors. Diponegoro who led the course of the Java War with his attitude and resistance to the colonial deserved high appreciation. In his resistance, Prince Diponegoro gained popular support as well as considerable involvement from the court which showed that Prince Diponegoro had considerable influence in the social life of society and the kingdom at that time. This rebellion was the first event of resistance faced by the Dutch Colonial Government which succeeded in changing the face of Java almost as a whole. The strategy and sacrifice given by Prince Diponegoro cannot be doubted. Although in the end the Prince Diponegoro succeeded in being defeated by the Dutch Colonial, this event had succeeded in fostering a spirit of unity and nationalism in the Javanese community.